2015
DOI: 10.2172/1215138
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the Integrated Expansion of the Canadian and U.S. Power Sectors with the Regional Energy Deployment System (ReEDS)

Abstract: System (ReEDS) model. The first portion of this report is focused on documenting augmentations made to the ReEDS model, building on prior work by Martinez et al. (2013). The work conducted and documented here aims to provide insights into the types of analysis this novel modeling capability can enable, rather than analyzing potential U.S-Canada power sector futures. The model is limited to long-term capacity expansion and high-levels steady-state operations and does not include detailed production cost of dyna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…In this paper, we document a development effort to update an endogenous treatment of the integrated U.S. -Canada electricity sectors in the NREL Regional Energy Deployment System (ReEDS) model. This effort is thoroughly documented in Martinez et al (2013) and Zinaman et al (2015). We also present results from an abbreviated scenario analysis, using this endogenous treatment, which demonstrates the new capability and yields initial insights into the influence of various drivers on power sector deployment.…”
Section: Introductionmentioning
confidence: 89%
See 2 more Smart Citations
“…In this paper, we document a development effort to update an endogenous treatment of the integrated U.S. -Canada electricity sectors in the NREL Regional Energy Deployment System (ReEDS) model. This effort is thoroughly documented in Martinez et al (2013) and Zinaman et al (2015). We also present results from an abbreviated scenario analysis, using this endogenous treatment, which demonstrates the new capability and yields initial insights into the influence of various drivers on power sector deployment.…”
Section: Introductionmentioning
confidence: 89%
“…The assumptions for the U.S. portion of the system are documented in NREL (2014). A more thorough description of these sources is included in Zinaman et al (2015).…”
Section: Data Sourcesmentioning
confidence: 99%
See 1 more Smart Citation
“…They solve for least-cost combinations of generation assets while being constrained by factors such as technology costs, unit availability and performance, as well as policy impacts and regulatory considerations [5]. ESPMs have been used to study the Canadian grid as a whole [3,6], specific regions [7,8], and the integration of Canadian and American grids [9][10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Dolter and Rivers [6] analyzed the costs of decarbonizing Canada's electricity system under different scenarios and concluded that Canada needs to increase carbon prices to achieve carbon reduction targets by 2030. Some studies that included Canada used an added fuel cost to represent carbon pricing systems while focusing on the impact of other regulatory measures [9][10][11][12]14], while others imposed GHG emissions constraints [8,13]. Notably, Doluweera et al [7] modelled the western provinces of Canada using a carbon cap and an added fuel cost in addition to other regulations.…”
Section: Introductionmentioning
confidence: 99%